Specific features of succession of a share in the right to joint tenancy - O. Ye. Kukhariev (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on clarifying specific features of the succession of a share in the right to joint tenancy, which is done in two stages. First, there is transformation of the legal regime of property – joint tenancy is modified into tenancy in common. And only after that, the share of the deceased co-owner is acquired by his/her lawful heirs within the inheritance procedure. Due to this fact, the author of the article has expressed own position that the object of succession is a share in the right to tenancy in common, but not to joint tenancy.